2000
DOI: 10.1086/501806
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Vancomycin-Resistant Enterococci in a Burn Unit

Abstract: A VRE outbreak in a BICU over 13 months was caused by a single clone. After apparent eradication of VRE from a BICU, recrudescence of the outbreak occurred, evidently from a small inapparent source of environmental contamination. Changes in gastrointestinal (GI) tract function (motility) and administration of medications, other than antibiotics, that have an effect on the GI tract may increase the risk of GI tract colonization by VRE in burn patients. Application of barrier isolation and an aggressive environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
114
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 31 publications
8
114
1
6
Order By: Relevance
“…Methicillin-resistant Staphylococcus aureus (MRSA) may exist on surfaces for as long as 360 days (37,38), and spore-forming bacteria, including Clostridium difficile, can survive for months. The longer a nosocomial pathogen persists on a surface, the longer it may be a source for transmission to a susceptible patient or HCW (5,13,17,21,26,29). Frequently touched surfaces such as doorknobs, push plates, bed rails, faucet handles, and poles supporting intravenous fluid supplies (IV poles) have been identified as reservoirs for the spread of pathogenic microbes (3,27) which can easily contaminate hands and equipment of HCWs, who, in turn, can transmit these pathogens to patients during routine care.…”
mentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) may exist on surfaces for as long as 360 days (37,38), and spore-forming bacteria, including Clostridium difficile, can survive for months. The longer a nosocomial pathogen persists on a surface, the longer it may be a source for transmission to a susceptible patient or HCW (5,13,17,21,26,29). Frequently touched surfaces such as doorknobs, push plates, bed rails, faucet handles, and poles supporting intravenous fluid supplies (IV poles) have been identified as reservoirs for the spread of pathogenic microbes (3,27) which can easily contaminate hands and equipment of HCWs, who, in turn, can transmit these pathogens to patients during routine care.…”
mentioning
confidence: 99%
“…The only other article 2 in the literature that included information on microbial growth on ECg lead wires was an epidemiological investigation of a 13-month-long VRE outbreak in a burn ICU that involved 21 patients. The investigators identified one instance in which a lead wire, swabbed as part of weekly patient surveillance, was positive for VRE.…”
mentioning
confidence: 99%
“…10,11 Maintenance of lowlevel endemicity after a large outbreak has been achieved 12,13 as has eradication following a small outbreak 14 and in specific units. [15][16][17] Successful control has also been reported in a healthcare region that included long-term-care facilities. 18 In that report, however, only 38 patients were found to be colonized during a 2-year period.…”
mentioning
confidence: 99%